Pengetahuan Ibu HIV Mempengaruhi Perilaku Pencegahan Penularan HIV/AIDS dari Ibu ke Bayi di Provinsi Jawa Tengah - Isni, Khoiriyah; Shaluhiyah, Zahroh; Cahyo, Kusyogo (Jurnal Promosi Kesehatan Indonesia, 2017)
Background: PMTCT was government program to suppres HIV/AIDS and child. The point of PMTCT activities was a strategy to prevent HIV/AIDS transmission from mothers living with HIV/AIDS to their child. However, there were mothers living with HIV/AIDS who have been too late knowing their status HIV status so that they did not join PMTCT.Method: This study aims to learn about HIV-positive mothers behavior in preventing of HIV/AIDS transmission from mother to child. This research was a quantitative with cross sectional approach. The data was collected from 32 mothers living with HIV/AIDS who had toddler babies in Central Java Province. Data were analyzed using univariate with frequency distribution, bivariate with chi square and fisher exact, and multivariate with logistic regression.Results: The result showed that the variable which correlated towards behavior of HIV-positive mothers in preventing HIV/AIDS transmission from mother to child were age of child, HIV status reveal time, time of joining ARV, joining PMTCT, time of joining PMTCT, and knowledge. While, knowledge was the main variable that has considerable influence on the behavior of HIV-positive mothers. From this research, can be conclude that knowledge can affect HIV-positive motherâ€™s behavior.Â